Culicidae-centric metabarcoding through targeted use of D2 ribosomal DNA primers - Pedro, Pedro M.; Amorim, Jandui; Rojas, Martha V.R.; Sá, Ivy Luizi; Galardo, Allan Kardec Ribeiro [UNESP]; Neto, Noel Fernandes Santos [UNESP]; de Carvalho, Dario Pires; Ribeiro, Kaio Augusto Nabas; Razzolini, Maria Tereza Pepe; Sallum, Maria Anice Mureb (PeerJ, 2020)
A practical limitation to many metabarcoding initiatives is that sampling methods tend to collect many non-target taxa, which become ‘‘amplicon noise’’ that can saturate Next Generation Sequencing results and lead to both financial and resource inefficiencies. An available molecular tool that can significantly decrease these non-target amplicons and decrease the need for pre-DNA-extraction sorting of bycatch is the design of PCR primers tailored to the taxa under investigation. We assessed whether the D2 extension segment of the 28S ribosomal operon can limit this shortcoming within the context of mosquito (Culicidae) monitoring. We designed PCR primers that are fully conserved across mosquitos and exclude from amplification most other taxa likely to be collected with current sampling apparatuses. We show that, given enough sequencing depth, D2 is an effective marker for the detection of mosquito sequences within mock genomic DNA pools. As few as 3,050 quality-filtered Illumina reads were able to recover all 17 species in a bulk pool containing as little as 0.2% of constituent DNA from single taxa. We also mixed these mosquito DNA pools with high concentrations of non-Culicidae bycatch DNA and show that the component mosquito species are generally still recoverable and faithful to their original relative frequencies. Finally, we show that there is little loss of fidelity in abundance parameters when pools from degraded DNA samples were sequenced using the D2 primers.
Keywords: Abundance estimates; D2 expansion segment; Metabarcoding; Mosquito monitoring; Non-target taxa